Indexing Structural Distortion : Sectoral Productivity, Structural Change and Growth - Ando, Sakai (IMF Working Papers; Working Paper, 2017)
This paper proposes a new index of sectoral labor distortion using employment and valueadded shares. We show that this index is highly correlated with growth both crosssectionally and over time. We also use it to compare the degree of distortion among countries and identify sectors where the potential payoffs in terms of growth from reforms could be large. The regression analysis in the paper shows that education and various structural reforms have potential to improve the efficiency of sectoral labor allocation.